Regulation of local L-type calcium channel signaling in anterior pituitary gonadotropes - Dang, An Khanh, author; Amberg, Greg, advisor; Clay, Colin, advisor; Tamkun, Michael, committee member; Navratil, Amy, committee member; Duval, Dawn, committee member (Colorado State University. Libraries, 2017)
The binding of gonadotropin-releasing hormone (GnRH) to its receptor initiates signaling cascades in gonadotropes which result in enhanced luteinizing hormone (LH) and follicle stimulating hormone (FSH) biosynthesis and secretion. Most dramatic is the sharp rise in LH secretion ("LH surge") that precedes and is necessary for follicular maturation and ovulation. Ca2+ influx activates mitogen-activated protein kinases (MAPKs) which lead to increased transcription of LH and FSH genes. Interestingly, previous research suggests that two MAPK signaling pathways, ERK and JNK, are activated by either Ca2+ influx through L-type Ca2+ channels or by global Ca2+ signals originating from intracellular stores, respectively. These discrete Ca2+ sources for divergent signaling cascades provides a mechanism in which gonadotropes can decode different pathways for appropriate gonadotropin release during various stages of the ovulatory cycle. However, direct evidence supporting an underlying subplasmalemmal local Ca2+ signaling through L-type Ca2+ channels distinct from intracellular Ca2+ was lacking. Here we used a combination of electrophysiology and total internal reflection fluorescence (TIRF) microscopy to visualize discrete sites of Ca2+ influx (Ca2+ sparklets) in gonadotrope-derived αT3-1 cells in real time. These localized GnRH-induced Ca2+ influxes are mediated by L-type Ca2+ channels and important for downstream ERK activation. In addition, precise structural and molecular elements to create a microenvironment suitable for localized subplasmalemmal L-type Ca2+ channel signaling was necessary for gonadotrope function, in which GnRH-dependent stimulation of L-type Ca2+ channel influx was found to require PKC and a dynamic actin cytoskeleton. More recently, we have further elucidated molecular mechanisms modulating localized L-type Ca2+ channel influx. Reactive oxygen species (ROS) are cognate signaling molecules that mediate cell function, but their role in regulating Ca2+ in gonadotropes is unknown. We have explored GnRH regulation of both NADPH oxidase complexes and mitochondrial sources of ROS and assessed ROS modulation of L-type Ca2+ channel activity in gonadotropes. We identified GnRH-induced spatially localized ROS "puncta" in αT3-1 cells, and ROS increased local Ca2+ channel activity in both αT3-1 cells and primary mouse gonadotropes. In addition, GnRH increased mitochondrial oxidation activity at the subplasmalemmal surface and mitochondrial ROS increased localized L-type Ca2+ channel influx. Also, active L-type Ca2+ channels were associated with subplasmalemmal mitochondria. Taken together, this dissertation explored the first direct evidence for localized L-type Ca2+ channel signaling in αT3-1 cells and elucidated signaling mechanisms in gonadotropes. Specifically, cellular organization via an intact cytoskeletal platform and ROS regulated L-type Ca2+ channel sparklet activity that are important for the downstream ERK activation and gonadotropin gene expression that regulates reproduction.
Keywords: gonadotrope; reactive oxygen species; GnRH; reproductive endocrinology; L-type calcium channel